EVALUASI KESESUAIAN LAHAN PERTANIAN KOMODITAS JAGUNG DI KECAMATAN SIPAHUTAR KABUPATEN TAPANULI UTARA - Nainggolan, Edoy; Fadilah, Rayhan; Sianturi, Jenni; Aceh, Resty Marhamah; Sianturi, Stevan Federico; Novira, Nina (Jurnal Tanah dan Sumberdaya Lahan, 2025)
Land evaluation is a process of assessing land resources to determine their suitability for specific purposes. This study aimed to evaluate the land suitability for maize (Zea mays L.) in Sipahutar District, North Tapanuli Regency, using a semi-detailed level analysis (1:50,000). The physical and environmental characteristics of the land were obtained from secondary data and analyzed using the matching method, which compared land characteristics with the optimal requirements for maize cultivation. The research area consisted of four land units (I-IV). The results indicated that land unit I fell within the N (unsuitable) class due to the limiting factor of sandy soil texture, that is difficult to overcome. Meanwhile, land units II-IV were classified as S3 (marginally suitable) due to limiting factors such as shallow rooting depth, which significantly affected productivity. These limitations are challenging to address without significant intervention, such as government support or investments from large-scale enterprises. The study highlights the need for targeted land management strategies to optimize maize production in the region.